Beating lady luck : effects of competitive gambling on opponent likeability and targeted physical aggression - Wee, Kenneth Z. (2019)
This study aimed to examine the effects of gambling motives and competitive gambling outcomes on opponent likeability and targeted physical aggression. We hypothesized that (a) losers would perceive their opponents to be less likeable and (b) would be physically more aggressive toward their opponents. Opponent likeability was proposed to mediate the lose–aggression relationship while social gambling motives were proposed to moderate the lose–aggression relationship. Specifically, we expected that losers of competitive gambling situations would engage in greater physical aggression only if they perceived their opponents to be less likeable. In addition, lower perceived opponent likeability would translate into greater targeted physical aggression only if the loser possessed low social motives for gambling. Ninety‐eight undergraduates who self‐identified mostly as recreational gamblers participated in a competitive gambling game. The Hot Sauce Paradigm was adapted as a measure of targeted physical aggression. Results obtained supported our hypotheses. Potential implications and limitations are discussed.